A multi-domain framework: A qualitative study evolving understanding of subject-matter in modelling educational games - Ahmad, M. (Institute of Electrical and Electronics Engineers Inc., 2015)
It is widely agreed that the traditional process of schooling can benefit from the usage of computers as supportive tools. Various approaches using computers in education have become the most prominent over the last decade (i.e. e-learning, game-based learning systems, and edutainment). A constant challenge has been faced by the game developers to achieve an effectively modelled and designed educational game. This can allow game developers to understand the relationships between game play (rules and regulations), game environment, learning theories, and the subject-matter (learner's achievement to achieve the objective of subject content) embedded in the educational game. Thus, the authors have proposed a multi-domain framework to conceptualize the elements with extracted implicit relationships through a systematic literature review. These relationships are verified through qualitative interviews with eight (8) game-based learning experts to validate the relationships. This paper presents eleven (11) implicit relationships based on subject-matter domain and discusses their relevancy with game environment, learning theories, and game play by applying interpretive hermeneutic approach of qualitative study. Consequently, this paper concludes eleven (11) explicit relationships for game developers to reflect on during the modelling and conceptualizing educational games in the development process. Â© 2015 IEEE.